Electrode foil for electrolytic capacitor, electrolytic capacitor, and method for producing electrolytic capacitor

By removing the natural oxidation coating on the surface of the anode body of the electrolytic capacitor and forming a second dielectric layer, the problem of reducing the electrostatic capacity of the existing capacitor is solved, and the improvement of the electrostatic capacity and the improvement of the capacitor performance is achieved.

CN115335937BActive Publication Date: 2025-04-01PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180022487.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-27
Filing Date
2021-01-29
Publication Date
2025-04-01
Estimated Expiration
2041-01-29

AI Technical Summary

Technical Problem

The surface of the anode body of the existing electrolytic capacitors is prone to form a natural oxidation coating, resulting in a decrease in the electrostatic capacity and the performance of the capacitor cannot be fully utilized.

Method used

The portion of the first dielectric layer is removed by atomic layer etching method or acid impregnation to form a second dielectric layer to cover the portion of the porous portion and increase the electrostatic capacity of the capacitor.

Benefits of technology

The reduction in the capacitance caused by the first dielectric layer is effectively suppressed, and the capacitance and performance of the electrolytic capacitor are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115335937B_ABST
    Figure CN115335937B_ABST
Patent Text Reader

Abstract

The electrode foil for electrolytic capacitors comprises: an anode body having a core and a porous portion provided on the surface of the core and containing a first metal; a first dielectric layer covering at least a portion of the porous portion; and a second dielectric layer covering at least a portion of the first dielectric layer. The second dielectric layer contains an oxide of the second metal. The first dielectric layer comprises: a dielectric having a thickness T 1 The first part, and having a thickness less than T 1 Thickness T 2 The second part of
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electrode foil for an electrolytic capacitor, an electrolytic capacitor, and a method for manufacturing an electrolytic capacitor. Background Art

[0002] The electrode foil of the electrolytic capacitor includes: an anode body and a dielectric layer covering the anode body. A substrate such as a metal foil containing a valve metal is used in the anode body. From the perspective of increasing the electrostatic capacitance, the surface of the substrate is roughened by etching or the like. That is, the anode body includes a core portion and a porous portion provided on the surface of the core portion, and the surface of the porous portion is covered with a dielectric layer. Regarding the electrode foil, various studies have been conducted on the materials used, etc. (for example, Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: International Publication No. 2015 / 118902 Summary of the invention

[0006] In view of the above situation, an electrode foil for an electrolytic capacitor according to one aspect of the present invention comprises: an anode body having a core portion and a porous portion provided on a surface of the core portion and containing a first metal; a first dielectric layer covering at least a portion of the porous portion; and a second dielectric layer covering at least a portion of the first dielectric layer and containing an oxide of a second metal, wherein the first dielectric layer comprises: a first portion having a thickness T1, and a second portion having a thickness T2 less than the thickness T1.

[0007] An electrolytic capacitor according to another aspect of the present invention includes: the electrode foil described above; and a solid electrolyte layer that covers at least a portion of the second dielectric layer of the electrode foil and contains a conductive polymer.

[0008] A method for manufacturing an electrolytic capacitor according to another aspect of the present invention includes: a first step of obtaining an anode body, wherein the anode body has a core portion and a porous portion provided on a surface of the core portion and contains a first metal, and at least a portion of the porous portion is covered by a first dielectric layer; a second step of removing at least a portion of the first dielectric layer by atomic layer etching or acid impregnation; and a third step of forming a second dielectric layer containing an oxide of a second metal in a manner covering at least a portion of the porous portion to obtain an electrode foil.

[0009] According to the present invention, an electrolytic capacitor having a large electrostatic capacitance can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1This is a cross-sectional view schematically showing a surface portion of an electrode foil according to one embodiment of the present invention.

[0011] Figure 2 It is a perspective view schematically showing the structure of a wound body included in an electrolytic capacitor according to an embodiment of the present invention.

[0012] Figure 3 1 is a cross-sectional view schematically showing an electrolytic capacitor according to an embodiment of the present invention. DETAILED DESCRIPTION

[0013] Hereinafter, before describing the embodiments, problems in the prior art will be briefly described.

[0014] Due to the placement of the anode body in the atmosphere, the surface (porous portion) of the anode body is in contact with the air, and a natural oxide film is easily formed on the surface of the anode body. In addition, the natural oxide film sometimes contains impurities from the anode body. Sometimes, due to the presence of the natural oxide film, the electrostatic capacitance cannot be fully obtained. In view of the above problems, the present invention provides an electrode foil for an electrolytic capacitor, an electrolytic capacitor, and a method for manufacturing an electrolytic capacitor for providing an electrolytic capacitor with a large electrostatic capacitance.

[0015] [Electrode foil for electrolytic capacitors]

[0016] The electrode foil for electrolytic capacitors of the present embodiment comprises: an anode body including a core portion and a porous portion provided on the surface of the core portion and including a first metal; a first dielectric layer covering at least a portion of the porous portion; and a second dielectric layer covering at least a portion of the first dielectric layer and including an oxide of a second metal. The first dielectric layer comprises: a first portion having a thickness T1 and a second portion having a thickness T2 less than the thickness T1.

[0017] The first dielectric layer includes a natural oxide film, and may include an oxide of the first metal derived from the anode body. In addition, the natural oxide film may also include impurities derived from the anode body. Sometimes, the electrostatic capacitance of the electrolytic capacitor cannot be fully obtained due to the natural oxide film.

[0018] In contrast, in the present invention, the thickness of a portion of the first dielectric layer is reduced from thickness T1 to thickness T2 by performing surface treatment based on the atomic layer etching (ALE) method or acid immersion to form the second portion. This suppresses the reduction in electrostatic capacitance caused by the first dielectric layer.

[0019] The porous portion may include: region A on the surface side of the anode body, and region B other than region A, and the first dielectric layer may include the second portion in region A and the first portion in region B. When the first dielectric layer includes the second portion in region A of the porous portion that is easily covered by the second dielectric layer, the influence of the first dielectric layer in region A is reduced, and the effect of the second dielectric layer is efficiently exerted, and it is easy to achieve the performance improvement of the electrolytic capacitor brought by the second dielectric layer. For example, by configuring a second dielectric layer with a high relative dielectric constant, it is easy to increase the capacity of the electrolytic capacitor.

[0020] The porous portion has a plurality of pits (holes), and the dielectric layer (the first dielectric layer and the second dielectric layer) covers the outer surface of the porous portion and the inner wall surface of the pit. The outer surface of the porous portion and the depth from the outer surface of the porous portion to the boundary between region A and region B (with the depth of Figure 1 The thickness D of area A A The inner wall surface of the pit between the depth corresponding to the thickness of T2 and the depth corresponding to the thickness of T2 can be covered by the first dielectric layer (second part). Figure 1 The thickness D of area A A corresponding depth) to the deepest part (with Figure 1 The inner wall surface of the pit between the depth corresponding to the thickness D0 of the porous portion and the depth corresponding to the thickness D1 of the porous portion may be covered by the first dielectric layer (first portion) with a thickness T1.

[0021] The first metal may include at least one selected from titanium (Ti), tantalum (Ta), niobium (Nb) and aluminum (Al). From the perspective of being more cost-effective, the first metal preferably includes Al. The first dielectric layer may include an oxide of the first metal. The oxide of the first metal (first dielectric layer) may include at least one selected from TiO2, Ta2O5, Nb2O5 and Al2O3.

[0022] The second metal may be the same as or different from the first metal. In the case where the second metal is different from the first metal, it will not be limited by the first metal, and a second metal that can form a second dielectric layer with a high relative dielectric constant can be selected, which makes it easy to increase the electrostatic capacitance of the electrolytic capacitor. In addition, the selection range of the second metal is expanded, so it is not limited by the first metal, and it is easy to give various properties to the second dielectric layer.

[0023] The second metal preferably includes at least one selected from tantalum (Ta), titanium (Ti), hafnium (Hf), zirconium (Zr), niobium (Nb), silicon (Si) and aluminum (Al). In this case, the oxide of the second metal has a high relative dielectric constant and is easy to increase the electrostatic capacitance. The oxide of the second metal (the second dielectric layer) preferably includes at least one selected from Ta2O5, TiO2, HfO2, ZrO2, Nb2O5, SiO2 and Al2O3. Among them, from the viewpoint of further improving the relative dielectric constant of the oxide of the second metal, the second metal is more preferably Ti and Nb. From the viewpoint of improving the withstand voltage, the second metal is more preferably Si, Zr, Hf, and Ta.

[0024] The second dielectric layer can be formed by atomic layer deposition (ALD). In this case, it is easy to form a dense and uniformly thick second dielectric layer. A second metal different from the first metal can be selected. In the case where the second dielectric layer contains two or more oxides of the second metal, each oxide can be mixed and can be formed in layers. From the perspective of increasing the capacity of the electrolytic capacitor, the oxide of the second metal preferably has a higher relative dielectric constant than the oxide of the first metal.

[0025] In the case of forming a thin and uniform second dielectric layer by the ALD method, in reality, there are sometimes macro defects such as pinholes and micro defects such as lattice defects on the surface of the pits in the porous portion (for example, the deep portion of the region B). The insulation is ensured by compensating the defects of the second dielectric layer with the first dielectric layer (the first part and the second part). In addition, the diffusion of the metal in the anode body into the second dielectric layer is suppressed by the first dielectric layer (the first part and the second part) formed by a covalent bond stronger than the metal bond in the anode body. If the metal in the anode body diffuses and is doped into the second dielectric layer, the relative dielectric constant and the insulation breakdown voltage may be reduced.

[0026] The composition of the oxide of the first metal contained in the first dielectric layer and the oxide of the second metal contained in the second dielectric layer can be obtained by performing elemental analysis based on energy dispersive X-ray spectroscopy (EDX) using a cross section of the electrode foil. When the second metal is different from the first metal, the first dielectric layer and the second dielectric layer can be distinguished by elemental mapping.

[0027] Below, refer to Figure 1 An example of the electrode foil according to the present embodiment will be described. Figure 1 Schematically shows a cross-sectional view of the surface portion of the electrode foil of this embodiment. Figure 1The first dielectric layer 120 (dashed line portion) in FIG. 1 represents the first dielectric layer before the surface treatment by the ALE method or acid dipping, and the first dielectric layer 121 (solid line portion) represents the first dielectric layer after the surface treatment by the ALE method or acid dipping.

[0028] The electrode foil (anode foil 10) includes an anode body 110 including a first metal, a first dielectric layer 121 covering at least a portion of the anode body 110, and a second dielectric layer (not shown) covering at least a portion of the first dielectric layer 121. The first dielectric layer 121 includes an oxide of the first metal derived from the anode body 110. The second dielectric layer includes an oxide of the second metal.

[0029] The anode body 110 can be obtained by roughening the surface of a metal foil containing a first metal by etching or the like, and has a core 111 and a porous portion 112 provided on the surface of the core 111. The first dielectric layer 121 covers at least a portion of the porous portion 112. The porous portion 112 has a plurality of pits (holes) 112P. The dielectric layers (the first dielectric layer 121 and the second dielectric layer) cover the outer surface of the porous portion 112 and the inner wall surface of the pit 112P. The first dielectric layer 121 can be formed to the surface of the deepest part of the pit 112P. The second dielectric layer can be formed to the surface of the deepest part of the pit 112P by, for example, the ALD method.

[0030] The first dielectric layer 121 includes: a first portion 121a having a thickness T1, and a second portion 121b having a thickness T2 less than the thickness T1. The porous portion 112 includes a region 112A on the surface side of the anode body 110, and a region 112B other than the region 112A (on the core 111 side). The first dielectric layer 121 includes the second portion 121b in region A (region 112A), and the first portion 121a in region B (region 112B). The second portion 121b is formed as follows: In region 112A, a portion of the first dielectric layer 120 having a thickness T1 is removed by surface treatment using an ALE method or acid immersion. The surface treatment using an ALE method or acid immersion is performed on the first dielectric layer covering the outer surface of the porous portion 112 and the inner wall surface of the pit 112P from the outer surface of the porous portion 112 to a certain depth, and the region 112A has a thickness D A .

[0031] The outer surface of the porous portion 112 and the boundary between the region 112A and the region 112B (with the thickness D of the region A) are A The inner wall surface of the pit 112P between the region 112A and the region 112B of the porous portion 112 (the thickness D corresponding to the region A) is covered by the second portion 121b.A The inner wall surface of the recess 112P between the deepest part (depth corresponding to the thickness D0 of the porous portion) and the deepest part (depth corresponding to the thickness D0 of the porous portion) is covered by the first portion 121a.

[0032] The thickness D0 of the porous portion 112 is, for example, not less than 1 / 10 and not more than 4 / 10 of the thickness of the anode body 110. The thickness D0 of the porous portion is obtained as follows: by using a cross-sectional image of the electrode foil obtained by a scanning electron microscope (SEM) or a transmission electron microscope (TEM), measuring the thickness of the porous portion at any 10 points, and calculating their average value.

[0033] The thickness D of the region 112A A The ratio (D A / D0)×100) can be 0.1% to 99.9%, or 50% to 99.9%, preferably 80% to 99.9%. When the ratio is 80% or more, it is easy to reduce the influence of the first dielectric layer and increase the electrostatic capacitance.

[0034] Thickness D of region A (region 112A) A It can be obtained by the following method.

[0035] The cross section of the electrode foil is observed by SEM or TEM, and a boundary portion (boundary between region A and region B) where the thickness of the first dielectric layer covering the inner wall of the pit changes sharply is confirmed between the outer surface of the porous portion and the deepest portion (depth corresponding to thickness D0). The distance (depth) in the thickness direction of the porous portion from the outer surface of the porous portion to the above-mentioned boundary portion is measured. Ten random points are confirmed on the above-mentioned boundary portion, and the above-mentioned distances (depths) are measured respectively. The average value thereof is calculated and used as the thickness D0 of region A. A In addition, the thickness D of the region A is subtracted from the thickness D0 of the porous portion. A The obtained value is taken as the thickness D of area B B .

[0036] The ratio of the thickness T2 of the second portion 121b to the thickness T1 of the first portion 121a: T2 / T1 is preferably 0.01 to 0.6, more preferably 0.01 to 0.1. In this case, the capacitance improvement effect due to the reduction in the thickness of the first dielectric layer from T1 to T2 is easily obtained.

[0037] The thickness T1 of the first part 121a can be, for example, greater than 1 nm and less than 10 nm. The thickness T2 of the second part 121b can be greater than 0.1 nm and less than 6 nm, or greater than 0.1 nm and less than 1 nm. When the thickness T2 is greater than 0.1 nm, it is easy to reduce the leakage current. It is easy to obtain the effect of ensuring insulation brought about by the first dielectric layer compensating for the defects of the second dielectric layer and the effect of suppressing the diffusion of metal in the anode body to the second dielectric layer brought about by the first dielectric layer. The thickness of the second dielectric layer is preferably greater than the thickness T2 of the second part 121b, and more preferably greater than the thickness T1 of the first part 121a. The thickness of the second dielectric layer is, for example, greater than 0.1 nm and less than 10 nm.

[0038] The thickness T2 of the second portion in the region A is obtained by measuring the thickness of any 10 points of the second portion in the region A using a cross-sectional image of the electrode foil by SEM or TEM and calculating their average value. The thickness T1 of the first portion in the region B is similarly obtained by measuring the thickness of any 10 points of the first portion in the region B and calculating their average value. The thickness of the second dielectric layer can also be obtained in the same manner.

[0039] [Electrolytic capacitors]

[0040] The electrolytic capacitor of this embodiment comprises: the electrode foil described above, and a solid electrolyte layer covering at least a portion of the second dielectric layer of the electrode foil. The solid electrolyte layer comprises a conductive polymer (π-conjugated polymer). The conductive polymer comprises polypyrrole, polythiophene, polyaniline, and derivatives thereof.

[0041] The electrolytic capacitor may also have a solvent. The solvent preferably includes a glycol compound and / or a glycerol compound (hereinafter also referred to as a glycol compound, etc.). The glycol compound, etc. may be included in the electrolyte described later. By making the solvent include a glycol compound, etc., the orientation or crystallinity of the π-conjugated polymer contained in the solid electrolyte layer can be improved. As a result, the conductivity of the solid electrolyte layer is improved, and the equivalent series resistance (ESR) of the electrolytic capacitor is reduced. In addition, the contact between the solid electrolyte layer and the second dielectric layer is improved, and the withstand voltage characteristics are improved.

[0042] The diol compound includes ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, and polyalkylene glycols having a molecular weight of about 190 to 400. The glycerol compound includes glycerol, polyglycerol, etc. The degree of polymerization of polyglycerol is preferably 2 or more and 20 or less. The diol compound may be used alone or in combination of two or more.

[0043] The electrolytic capacitor may further include an electrolyte solution. By using the electrolyte solution, an electrolytic capacitor having an excellent repair function of the dielectric layer can be obtained. The electrolyte solution includes, for example, a solvent and an ionic substance (solute, such as an organic salt) dissolved in the solvent.

[0044] The solvent may be an organic solvent or an ionic liquid. As the solvent, a high boiling point solvent is preferred. For example, carbonate compounds such as propylene carbonate, cyclic sulfones such as sulfolane, lactones such as γ-butyrolactone, amides such as N-methylacetamide, N,N-dimethylformamide, N-methyl-2-pyrrolidone, esters such as methyl acetate, ethers such as 1,4-dioxane, ketones such as methyl ethyl ketone, formaldehyde, etc. may be used. The solvent may be used alone or in combination of two or more.

[0045] An organic salt refers to a salt in which at least one of an anion and a cation contains an organic substance. As the organic salt, for example, trimethylamine maleate, triethylamine borodisalicylate, ethyldimethylamine phthalate, 1,2,3,4-tetramethylimidazolinium phthalate, 1,3-dimethyl-2-ethylimidazolinium phthalate, etc. can be used. One organic salt may be used alone or two or more may be used in combination.

[0046] [Method for manufacturing electrolytic capacitor]

[0047] The manufacturing method of the electrolytic capacitor of the present embodiment includes: a first step of obtaining an anode body including a first metal. The anode body has a core portion and a porous portion provided on the surface of the core portion, and at least a portion of the porous portion is covered by a first dielectric layer. The above-mentioned manufacturing method further includes: a second step of removing at least a portion of the first dielectric layer by atomic layer etching (ALE) or acid impregnation; and a third step of forming a second dielectric layer in a manner covering at least a portion of the porous portion to obtain an electrode foil.

[0048] By removing at least a portion of the first dielectric layer in the second step, the influence of the first dielectric layer is reduced, and the reduction in capacity caused by the first dielectric layer is suppressed. By reducing the influence of the first dielectric layer, the second dielectric layer formed in the third step can be effectively exerted, and the performance improvement of the electrolytic capacitor brought by the second dielectric layer can be easily achieved.

[0049] Hereinafter, each step will be described in detail.

[0050] (First process)

[0051] The anode body is usually obtained by roughening the surface of a substrate such as a metal foil containing a first metal by etching or the like. The metal foil may be a foil of the first metal or an alloy foil containing the first metal. The thickness of the metal foil is not particularly limited, for example, it is greater than 15 μm and less than 300 μm. A plurality of pits are formed on the surface of the metal foil by roughening. At least a portion of the porous portion of the anode body is covered by a first dielectric layer. The first dielectric layer includes a natural oxide film, which can be formed by natural oxidation of the surface of the metal foil. The natural oxide film can be formed to the surface of the deepest part of the pit.

[0052] The pore size of the pit formed on the surface of the metal foil is not particularly limited. From the perspective of being able to increase the surface area and the second dielectric layer being easily formed to the depth of the pit, it is preferably 50 nm or more and 2000 nm or less. The pore size of the pit refers to, for example, the highest frequency pore size of the pore distribution measured by a mercury porosimeter. The depth of the pit is also not particularly limited and can be appropriately set according to the thickness of the metal foil. Among them, from the perspective of being able to increase the surface area and maintaining the strength of the electrode foil, the thickness D0 of the etching area (porous portion) forming the pit is preferably 1 / 10 or more and 4 / 10 or less of the thickness of the metal foil before etching.

[0053] (Second process)

[0054] In the second step, at least a portion of the first dielectric layer is removed by the ALE method or acid impregnation. By the ALE method, a thin layer of the first dielectric layer can be removed in atomic layer units. In the ALE method, etching is performed using a reactive gas, so the first dielectric layer can be removed until the deepest part of the porous part (pit) with a complex structure. In the ALE method, the self-limiting effect plays a role, and etching can be performed in atomic layer units. The etching rate is the same on the outer surface side and the deepest side of the porous part, and it is easy to make the etching depth (the thickness of the first dielectric layer removed) uniform. In the acid impregnation, the first dielectric layer is dissolved and removed by immersing in the acid for a certain period of time. The solution used in the acid impregnation is, for example, sulfuric acid, nitric acid / phosphoric acid / oxalic acid or at least one of their salts. The hydrogen ion concentration of the solution used in the acid impregnation is in the range of 0.5 mol / L or more and 2.5 mol / L or less, and is preferably in the range of 1.0 mol / L or more and 2.0 mol / L or less. When the hydrogen ion concentration is too high, it will dissolve to the core of the anode body and the porous part provided on the surface of the core, so the porosity is reduced and sufficient electrostatic capacitance cannot be obtained. On the other hand, when the hydrogen ion concentration is too low, the effect of dissolving the first dielectric layer cannot be fully obtained. The temperature of the solution used in the acid impregnation is in the range of 25°C to 70°C, preferably in the range of 35°C to 65°C. When the temperature is too high, it will dissolve to the core of the anode body and the porous part provided on the surface of the core, so the porosity is reduced and sufficient electrostatic capacitance cannot be obtained. On the other hand, when the temperature is too low, the effect of dissolving the first dielectric layer cannot be fully obtained. The time for acid impregnation is in the range of 30 seconds to 300 seconds, preferably in the range of 60 seconds to 250 seconds. When the impregnation time is too long, it will dissolve to the core of the anode body and the porous part provided on the surface of the core, so the porosity is reduced and sufficient electrostatic capacitance cannot be obtained. On the other hand, if the immersion time is too short, the effect of dissolving the first dielectric layer cannot be sufficiently obtained. Acid immersion can be realized at a low cost compared to the ALE method.

[0055] The entire first dielectric layer may be completely removed by the second step, or a portion of the first dielectric layer may remain slightly thin without being removed.

[0056] In the second step, the entire area of ​​the porous portion (the outer surface of the porous portion and the entire inner wall surface of the pit) may be subjected to surface treatment using the ALE method or acid immersion. Alternatively, the surface side area A of the anode body of the porous portion (the outer surface of the porous portion and a certain depth from the outer surface of the porous portion (with a certain depth of 1.5 mm) may be subjected to surface treatment using the ALE method or acid immersion. Figure 1 Thickness D A The inner wall surface of the pit at the corresponding depth) is surface treated by ALE method or acid immersion.

[0057] In the ALE method, a chemical modification process that acts only on the outermost atomic layer of the object and an etching process that removes only the chemically modified portion are repeated alternately. The thickness of the first dielectric layer removed can be controlled by the number of times (cycles) the chemical modification process and the etching process are repeated. The chemical modification process and the etching process can be performed by supplying a reaction gas into a reaction chamber in which the object is arranged.

[0058] An example of a case where an anode body whose surface of a porous portion is covered by a first dielectric layer is subjected to a surface treatment using an ALE method is shown below. Here, the following case is shown: the first dielectric layer is an Al2O3 layer, the reaction gas (first reaction material) supplied in the chemical modification process is HF, and the reaction gas (second reaction material) supplied in the etching process is Al(CH3)3.

[0059] First, in the chemical modification step, the Al2O3 layer is brought into contact with HF gas. At this time, the fluorination reaction of the following formula (1) proceeds, AlF3 is generated together with water vapor, and a portion (atomic layer) of the outermost surface of the Al2O3 layer is modified by AlF3.

[0060] Al2O3+6HF→2AlF3+3H2O (1)

[0061] Next, in the etching process, the formed AlF3 atomic layer is brought into contact with Al(CH3)3 gas. At this time, the ligand exchange reaction of the following formula (2) proceeds to generate a volatile substance of AlF(CH3)2, and the AlF3 atomic layer is removed.

[0062] AlF3+2Al(CH3)3→3AlF(CH3)2 (2)

[0063] The chemical modification step and the etching step are repeated alternately. The chemical modification step and the etching step are performed at a temperature of, for example, 100° C. to 400° C. In this case, thermal damage to the metal foil is suppressed. The first reaction material may also use fluorine-containing materials such as F2, CF4, NF3, ClF3, and XeF2 other than HF.

[0064] The second reaction material may also use an alkyl metal complex other than Al(CH3)3, β-diketone metal complex such as tin(II) acetylacetonate: Sn(acac)2, etc. In the case where the second reaction material is Sn(acac)2, a volatile substance of SnF(acac)2 and Al(acac)3 is generated by the ligand exchange reaction of the following formula (3), and the atomic layer of AlF3 is removed.

[0065] AlF3+3Sn(acac)2→Al(acac)3+3SnF(acac)2 (3)

[0066] The chemical modification step and the etching step can be performed by supplying reaction gases (the first reaction material and the second reaction material) into the reaction chamber where the anode body is arranged. A (The depth from the outer surface of the porous portion reached by the surface treatment using the ALE method) can be controlled by, for example, the amount of gas supplied into the reaction chamber (gas concentration), the temperature and pressure in the reaction chamber, and the like.

[0067] In the second step, the thickness of at least a portion of the first dielectric layer may be reduced from thickness T1 to thickness T2 by ALE or acid immersion. The thickness T1 of the first dielectric layer may be determined by measuring the thickness of any 10 points of a cross-sectional image of the first dielectric layer based on SEM or TEM before the surface treatment by ALE and calculating the average value thereof. The thickness T2 of the first dielectric layer after the surface treatment by ALE may be determined in the same manner.

[0068] In the second step, the thickness of the first dielectric layer can be reduced from thickness T1 to thickness T2 in at least region A on the surface side of the anode body of the porous portion by ALE or acid impregnation. A The ratio of the thickness D0 of the porous part (D A / D0)×100) can be, for example, 0.1% or more and 99.9% or less, or 50% or more and 99.9% or less, preferably 80% or more and 99.9% or less. The ratio of thickness T2 to thickness T1: T2 / T1 is preferably 0.01 or more and 0.6 or less, more preferably 0.01 or more and 0.1 or less. Thickness T2 can be 0.1nm or more and 6nm or more and 0.1nm or more and 1nm or less. Thickness T1 can be 1nm or more and 10nm or less.

[0069] (Third process)

[0070] In the third step, a second dielectric layer including an oxide of a second metal is formed so as to cover at least a portion of the first dielectric layer. The porous portion of the anode body is covered by the second dielectric layer directly or via the first dielectric layer.

[0071] In the third step, the second dielectric layer is preferably formed by atomic layer deposition (ALD). In the ALD method, a dense and uniform second dielectric layer can be formed. In the ALD method, when the thickness of the second dielectric layer is obtained, the deviation of the thickness values ​​of the second dielectric layer at 10 positions measured is small, and the standard deviation is, for example, less than 0.5 nm.

[0072] The ALD method is a film-forming method in which a raw material gas containing a second metal and an oxidant are alternately supplied to a reaction chamber in which an object is arranged, and a second dielectric layer containing an oxide of the second metal is formed on the surface of the object. In the ALD method, a self-limiting effect is exerted, so that the second metal is deposited on the surface of the object in atomic layer units. Therefore, the thickness of the second dielectric layer is controlled by taking the supply of raw material gas → exhaust (purge) of raw material gas → supply of oxidant → exhaust (purge) of oxidant as one cycle. That is, the ALD method can easily control the thickness of the formed second dielectric layer.

[0073] It should be noted that, while CVD is generally performed at a temperature of 400 to 900° C., the ALD method can be performed at a temperature of 100 to 400° C. That is, the ALD method is excellent in that thermal damage to the metal foil can be suppressed.

[0074] Examples of the oxidant used in the ALD method include water, oxygen, ozone, etc. The oxidant can be supplied to the reaction chamber in the form of plasma using the oxidant as a raw material.

[0075] The second metal is supplied to the reaction chamber in the form of a gas containing a precursor of the second metal. The precursor is, for example, an organic metal compound containing the second metal, whereby the second metal is easily chemically adsorbed to the object. As the precursor, various organic metal compounds used in the ALD method can be used.

[0076] Examples of the precursor containing Al include trimethylaluminum ((CH 3 ) 3 Al) and triethylaluminum ((C 2 H 5 ) 3 Al).

[0077] Examples of the precursor containing Ta include (tert-butylimide)tris(ethylmethylamino)tantalum(V) (C 13 H 33 N4Ta, TBTEMT), pentaethoxide tantalum (V) (Ta(OC2H5)5), (tert-butylimide)tris(diethylamino)tantalum (V) ((CH3)3CNTa(N(C2H5)2)3), penta(dimethylamino)tantalum (V) (Ta(N(CH3)2)5), etc.

[0078] Examples of the precursor containing Nb include niobium (V) ethoxide (Nb(OCH2CH3)5, tris(diethylamide)(tert-butylimide)niobium (V) (C 16 H 39 N4Nb) etc.

[0079] Examples of the precursor containing Si include: N-sec-butyl(trimethylsilyl)amine (C7H19 NSi), 1,3-diethyl-1,1,3,3-tetramethyldisilazane (C8H 23 NSi2), 2,4,6,8,10-pentamethylcyclopentasiloxane ((CH3SiHO)5), pentamethyldisilane ((CH3)3SiSi(CH3)2H), tri(isopropoxy)silanol ([(H3C)2CHO]3SiOH), chloropentamethyldisilane ((CH3)3SiSi(CH3)2Cl), dichlorosilane (SiH2Cl2), tri(dimethylamino)silane (Si[N(CH3)2]4), tetraethylsilane (Si(C2H5)4), tetramethylsilane (Si(CH3)4), tetraethoxysilane (Si(OC2H5)4), dodecamethylcyclohexasilane ((Si(CH3)2)6), silicon tetrachloride (SiCl4), silicon tetrabromide (SiBr4), etc.

[0080] Examples of the precursor containing Ti include bis(tert-butylcyclopentadienyl)titanium(IV) dichloride (C 18 H 26 Cl2Ti), tetrakis(dimethylamino)titanium(IV) ([(CH3)2N]4Ti, TDMAT), tetrakis(diethylamino)titanium(IV) ([(C2H5)2N]4Ti), tetrakis(ethylmethylamino)titanium(IV) (Ti[N(C2H5)(CH3)]4), (diisopropoxybis(2,2,6,6-tetramethyl-3,5-heptanedione)titanium(IV) (Ti[OCC(CH3)3CHCOC(CH3)3]2(OC3H7)2), titanium tetrachloride (TiCl4), isopropoxide titanium(IV) (Ti[OCH(CH3)2]4), ethoxide titanium(IV) (Ti[O(C2H5)]4), etc.

[0081] Examples of the precursor containing Zr include: bis(methyl-η 5 Cyclopentadienyl) methoxymethyl zirconium (Zr(CH3C5H4)2CH3OCH3), tetrakis(dimethylamide) zirconium (IV) ([(CH3)2N]4Zr), tetrakis(ethylmethylamide) zirconium (IV) (Zr(NCH3C2H5)4), tert-butyl zirconium (IV) (Zr[OC(CH3)3]4), etc.

[0082] As precursors containing Hf, for example, there can be mentioned: hafnium tetrachloride (HfCl4), tetrakis dimethylamino hafnium (Hf[N(CH3)2]4), tetrakis diethylamino hafnium (Hf[N(C2H5)(CH3)]4), tetrakis diethylamino hafnium (Hf[N(C2H5)2]4), hafnium tert-butoxide (Hf[OC(CH3)3]4), etc.

[0083] (Fourth process)

[0084] The manufacturing method of the electrolytic capacitor described above may include: a fourth step of forming a solid electrolyte layer containing a conductive polymer in a manner that covers at least a portion of the second dielectric layer of the electrode foil. The solid electrolyte layer can be formed, for example, by chemically polymerizing and / or electrolytically polymerizing the raw material monomer on the second dielectric layer of the electrode foil. In addition, the solid electrolyte layer can be formed by applying a solution in which a conductive polymer is dissolved or a dispersion in which a conductive polymer is dispersed to the second dielectric layer of the electrode foil. After the fourth step (after forming the solid electrolyte layer), a solvent or an electrolyte can be further impregnated into the electrode foil.

[0085] In the case where the anode body having the dielectric layer is Figure 1 In the case of the electrode foil (anode foil) shown in FIG. 1 , the electrode foil (anode foil) can be made before the fourth step as shown in FIG. Figure 2 The wound body 100 is shown. Figure 2 It is a development view for explaining the structure of the wound body 100 .

[0086] When the winding body 100 is produced, in addition to the anode foil 10, a cathode foil 20 is also prepared. The cathode foil 20 can use a metal foil like the anode foil 10. The type of metal constituting the cathode foil 20 is not particularly limited, and a valve metal such as Al, Ta, Nb or an alloy containing a valve metal can be used. The surface of the cathode foil 20 can be roughened as needed.

[0087] Next, the anode foil 10 and the cathode foil 20 are wound with the separator 30 interposed therebetween. One end of the lead tab 50A or 50B is connected to each of the anode foil 10 and the cathode foil 20, and the lead tabs 50A and 50B are wound to form the wound body 100. The other ends of the lead tabs 50A and 50B are connected to the leads 60A and 60B, respectively.

[0088] The separator 30 is not particularly limited, and for example, nonwoven fabric mainly composed of cellulose, polyethylene terephthalate, vinylon, aramid fiber, or the like can be used.

[0089] Next, a stopper tape 40 is disposed on the outer surface of the cathode foil 20 located at the outermost layer of the wound body 100, and the end of the cathode foil 20 is fixed by the stopper tape 40. It should be noted that when the anode foil 10 is prepared by cutting from a large-sized foil, the wound body 100 may be further subjected to a chemical conversion treatment in order to provide a dielectric layer on the cut surface.

[0090] The wound body 100 is impregnated with a solution in which a conductive polymer is dissolved or a dispersion in which a conductive polymer is dispersed, and a solid electrolyte layer is formed between the anode foil 10 and the cathode foil 20. The wound body 100 after the solid electrolyte layer is formed may be further impregnated with an electrolyte. As the impregnation method of the solution, for example, there can be cited a method of immersing the wound body 100 in a solution contained in a container, a method of dripping a solution on the wound body 100, etc. The impregnation can be performed under reduced pressure, for example, in an atmosphere of 10 kPa to 100 kPa, preferably 40 kPa to 100 kPa.

[0091] Next, by sealing the wound body 100, a Figure 3 To manufacture the electrolytic capacitor 200, first, the wound body 100 is housed in the bottomed case 211 so that the leads 60A and 60B are located on the opening side of the bottomed case 211. As the material of the bottomed case 211, a metal such as aluminum, stainless steel, copper, iron, brass, or an alloy thereof can be used.

[0092] Next, the sealing member 212 formed in a manner that the leads 60A and 60B pass through is arranged above the winding body 100, and the winding body 100 is sealed in the bottom shell 211. The sealing member 212 can be any insulating material, preferably an elastomer. Among them, silicone rubber, fluororubber, ethylene-propylene rubber, Hypalon (trademark) rubber, butyl rubber, isoprene rubber, etc. with high heat resistance are preferred.

[0093] Next, the open end of the bottomed housing 211 is subjected to transverse necking, and the open end is riveted to the sealing member 212 to be curled. Finally, the seal is completed by placing a seat plate 213 on the curled portion. Then, an aging treatment can be performed while applying a rated voltage.

[0094] In the above-mentioned embodiment, the winding type electrolytic capacitor is described, but the application scope of the present invention is not limited to the above content, and it can also be applied to other electrolytic capacitors, for example, a laminated electrolytic capacitor.

[0095] [Example]

[0096] Hereinafter, the present invention will be described in more detail based on Examples, but the present invention is not limited to the Examples.

[0097] 《Example 1》

[0098] A wound electrolytic capacitor (Φ (diameter) 6.3 mm×L (length) 9.9 mm) with a rated voltage of 2.0 V was produced. A specific method for producing the electrolytic capacitor will be described below.

[0099] (Manufacturing of anode foil)

[0100] (First process)

[0101] Prepare Al foil with a thickness of 100 μm. Perform DC etching on the Al foil to roughen the surface and obtain an anode body. An etching area (porous portion) with a thickness of 40 μm is formed on the surface of the Al foil, and the pore size of the pits is 100 to 200 nm. The Al foil (anode body) with a roughened surface is placed in the atmosphere for 168 hours. On the surface of the Al foil, a first dielectric layer (natural oxide film) with a thickness of 10 nm is formed in a manner that covers the fine uneven surface of the Al foil.

[0102] (Second process)

[0103] A portion of the first dielectric layer was removed by the ALE method (first reaction material: HF, second reaction material: Al(CH3)3, temperature: 300°C, pressure: 1Pa). At this time, the thickness of the first dielectric layer was reduced from thickness T1 to thickness T2 in region A from the outer surface of the porous portion to a certain depth. The number of cycles of the ALE method (chemical modification step and etching step) was adjusted so that the thickness T2 became the value shown in Table 1.

[0104] (Third process)

[0105] The second dielectric layer was formed by the ALD method (precursor: [(CH3)2N]4Ti, oxidant: O3, temperature: 300°C, pressure: 1Pa) so as to cover the first dielectric layer. The number of ALD cycles was adjusted so that the thickness of the second dielectric layer became the value shown in Table 1. In this way, an anode body (anode foil) having the first dielectric layer and the second dielectric layer in sequence on the surface was obtained. The anode foil was then cut into a specified size.

[0106] EDX analysis confirmed that the second dielectric layer was a TiO2 layer and the first dielectric layer was an Al2O3 layer. The thickness D0 of the porous portion obtained by the above method was 40 μm, and the thickness D of the region A of the porous portion was 1.3 μm. A The thickness D of region A is 36 μm. A The ratio of the thickness D0 of the porous portion to the thickness T2 of the second portion of the first dielectric layer in region A obtained by the above method is 0.1 nm, and the thickness T1 of the first portion of the first dielectric layer in region B is 10 nm. T2 / T1 is 0.01. The thickness of the second dielectric layer obtained by the above method is 15.6 nm.

[0107] (Manufacturing of cathode foil)

[0108] An Al foil having a thickness of 50 μm was etched to roughen the surface of the Al foil, thereby obtaining a cathode foil. The cathode foil was then cut into a predetermined size.

[0109] (Production of wound body)

[0110] The anode lead connector and the cathode lead connector are connected to the anode foil and the cathode foil, and the anode foil and the cathode foil are wound with the spacer while the lead connector is wound in. The anode lead and the cathode lead are respectively connected to the ends of each lead connector protruding from the wound body. Then, the prepared wound body is chemically converted again, and a dielectric layer is formed at the cut end of the anode foil. Next, the end of the outer surface of the wound body is fixed with a stop tape.

[0111] (Preparation of Conductive Polymer Dispersion Liquid)

[0112] A mixed solution was prepared by dissolving 3,4-ethylenedioxythiophene and polystyrene sulfonic acid as a dopant in ion exchange water. While stirring the obtained mixed solution, iron (III) sulfate (oxidant) dissolved in ion exchange water was added to carry out a polymerization reaction. After the reaction, the obtained reaction solution was dialyzed to remove unreacted monomers and excess oxidant, thereby obtaining a conductive polymer dispersion containing about 5% by mass of polyethylenedioxythiophene doped with polystyrene sulfonic acid.

[0113] (Formation of Solid Electrolyte Layer)

[0114] In a reduced pressure atmosphere (40 kPa), the wound body was immersed in a conductive polymer dispersion contained in a specified container for 5 minutes, and then the wound body was lifted out of the conductive polymer dispersion. Next, the wound body impregnated with the conductive polymer dispersion was dried in a drying oven at 150°C for 20 minutes, and a solid electrolyte layer containing a conductive polymer was formed between the anode foil and the cathode foil.

[0115] (Sealing of wound body)

[0116] The wound body with the solid electrolyte layer is sealed and completed. Figure 3 The electrolytic capacitor shown in the figure was then aged at 130°C for 2 hours while applying the rated voltage.

[0117] 《Examples 2 to 5》

[0118] In the production of the anode foil, the number of cycles of the ALE method was changed so that the thickness T2 of the second portion of the first dielectric layer became the value shown in Table 1. The number of cycles of the ALD method was changed so that the thickness of the second dielectric layer became the value shown in Table 1. Except for the above, an electrolytic capacitor was produced by the same method as in Example 1.

[0119] Comparative Example 1

[0120] In the production of the anode foil, the anode body whose surface is covered by the first dielectric layer was not subjected to the surface treatment by the ALE method (second step). By changing the number of ALD cycles, the thickness of the second dielectric layer was set to the value shown in Table 1. Except for the above, an electrolytic capacitor was produced by the same method as in Example 1.

[0121] [evaluate]

[0122] The electrostatic capacitance of the electrolytic capacitor obtained above was measured. The electrostatic capacitance was expressed as an index (relative value) with the electrostatic capacitance of the electrolytic capacitor of Comparative Example 1 being 1. The evaluation results are shown in Table 1.

[0123] [Table 1]

[0124]

[0125] The electrolytic capacitors of Examples 1 to 5 had larger electrostatic capacitances than the electrolytic capacitor of Comparative Example 1. In particular, in Examples 1 and 2, larger electrostatic capacitances were obtained.

[0126] Industrial Applicability

[0127] The electrode foil of the present invention can be used in capacitors for various purposes because its capacitance is increased.

[0128] Description of Reference Numerals

[0129] 10: Anode foil, 20: Cathode foil, 30: Spacer, 40: Anti-winding tape, 50A, 50B: Lead tabs, 60A, 60B: Leads, 100: Wound body, 110: Anode body, 111: Core, 112: Porous portion, 112P: Pits, 112A: A region on the surface side of the anode body in the porous portion, 112B: A region on the core side of the porous portion, 120: First dielectric layer before surface treatment using the ALE method, 121: First dielectric layer after surface treatment using the ALE method, 121a: First portion of the first dielectric layer, 121b: Second portion of the first dielectric layer, 200: Electrolytic capacitor, 211: Bottom casing, 212: Sealing member, 213: Seat plate

Claims

1. An electrode foil for an electrolytic capacitor, comprising: an anode body having a core portion and a porous portion provided on a surface of the core portion and containing a first metal; a first dielectric layer covering at least a portion of the porous portion; and a second dielectric layer covering at least a portion of the first dielectric layer and comprising an oxide of a second metal, The first dielectric layer includes: a first portion having a thickness T1 and a second portion having a thickness T2 smaller than the thickness T1. The porous portion includes a region A on the surface side of the anode body and a region B other than the region A. The first dielectric layer has the second portion in the region A and the first portion in the region B, The porous portion has a plurality of pits, and the outer surface of the porous portion and the inner wall surfaces of the pits from the outer surface of the porous portion to the depth of the boundary between region A and region B are covered by the second portion with a thickness of T2, and the inner wall surfaces of the pits from the depth of the boundary between region A and region B of the porous portion to the deepest portion are covered by the first portion with a thickness of T1.

2. The electrode foil for electrolytic capacitor according to claim 1, wherein The region A has a thickness D of not less than 0.1% and not more than 99.9% of the thickness D0 of the porous portion. A .

3. The electrode foil for electrolytic capacitor according to claim 1, wherein A ratio of the thickness T2 to the thickness T1: T2 / T1 is greater than or equal to 0.01 and less than or equal to 0.

6.

4. The electrode foil for electrolytic capacitor according to claim 1, wherein The thickness T2 is greater than or equal to 0.1 nm and less than or equal to 6 nm.

5. The electrode foil for electrolytic capacitor according to claim 1, wherein The thickness T1 is greater than or equal to 1 nm and less than or equal to 10 nm.

6. The electrode foil for electrolytic capacitor according to claim 1, wherein The first dielectric layer includes an oxide of the first metal.

7. The electrode foil for electrolytic capacitor according to claim 1, wherein The first metal includes at least one selected from titanium, tantalum, niobium and aluminum.

8. The electrode foil for electrolytic capacitor according to any one of claims 1 to 7, wherein The second metal includes at least one selected from tantalum, titanium, hafnium, zirconium, niobium, silicon and aluminum.

9. An electrolytic capacitor comprising: The electrode foil according to any one of claims 1 to 8; and A solid electrolyte layer covers at least a portion of the second dielectric layer of the electrode foil and includes a conductive polymer. 10 . The electrolytic capacitor according to claim 9 , further comprising a solvent or an electrolyte solution.

11. A method for manufacturing an electrolytic capacitor, comprising: In a first step, an anode body is obtained, wherein the anode body has a core portion and a porous portion provided on a surface of the core portion and contains a first metal, and at least a portion of the porous portion is covered by a first dielectric layer; A second step of reducing the thickness of the first dielectric layer from thickness T1 to thickness T2 in a region A on the surface side of the anode body of the porous portion by atomic layer etching or acid immersion; as well as In a third step, a second dielectric layer including an oxide of a second metal is formed so as to cover at least a portion of the porous portion to obtain an electrode foil. The porous portion includes a region A on the surface side of the anode body and a region B excluding the region A. In the region B, the thickness of the first dielectric layer is T1.

12. The method for manufacturing an electrolytic capacitor according to claim 11, wherein: The region A has a thickness D of not less than 0.1% and not more than 99.9% of the thickness D0 of the porous portion. A .

13. The method for manufacturing an electrolytic capacitor according to claim 11, wherein: A ratio of the thickness T2 to the thickness T1: T2 / T1 is greater than or equal to 0.01 and less than or equal to 0.

6.

14. The method for manufacturing an electrolytic capacitor according to claim 11, wherein: The thickness T2 is greater than or equal to 0.1 nm and less than or equal to 6 nm.

15. The method for manufacturing an electrolytic capacitor according to claim 11, wherein: The thickness T1 is greater than or equal to 1 nm and less than or equal to 10 nm.

16. The method for manufacturing an electrolytic capacitor according to any one of claims 11 to 15, wherein: The first dielectric layer includes an oxide of the first metal.

17. The method for manufacturing an electrolytic capacitor according to any one of claims 11 to 15, wherein: The first metal includes at least one selected from titanium, tantalum, niobium and aluminum.

18. The method for manufacturing an electrolytic capacitor according to any one of claims 11 to 15, wherein: The second metal includes at least one selected from tantalum, titanium, hafnium, zirconium, niobium, silicon and aluminum.

19. The method for manufacturing an electrolytic capacitor according to any one of claims 11 to 15, wherein: In the third step, the second dielectric layer is formed by atomic layer deposition.

Citation Information

Patent Citations

  • Capacitor

    WO2015118902A1

  • Noiseless rain shutter door

    JP1995082968A

  • Electrode foil for electrolytic capacitor, electrolytic capacitor, and methods for manufacturing same

    WO2019167773A1